There was an old lady who picked a pumpkin! - Colandro, Lucille; Lee, Jared (New York, NY Scholastic Inc., 2023)
"The Old Lady is back for a fall adventure--now in our bestselling reader format!"--
112435
Keywords: Older women -- Juvenile fiction; Autumn -- Juvenile fiction; Pumpkin -- Juvenile fiction; Stories in rhyme; Picture books; Readers (Elementary); Stories in rhyme; Picture books